Building integration of solar thermal systems-example of a refurbishment of a church rectory. (July 2019) - Cristofari, C.; Carutasiu, M.B.; Canaletti, J.L.; Norvaišienė, R.; Motte, F.; Notton, G.
Abstract: Given the fact that the solar industry is relatively mature, and the costs of equipment are stabilized, the utilization of solar thermal equipment in reducing the energy consumption in buildings increased. For this reason, in the frame of the present work, a new flat plate solar collector (H2OSS ® ) and a new solar air collector (Volet'air ® ) with high building integration were analyzed. Moreover, in concordance with the goals of European Project "Maritimo", which implies refurbishing the Mediterranean houses, this Paper presents the energy reduction resulted from integrating these solar systems. They were used to refurbish a building placed in Bocognano, Corsica, France, near the center of the island. The performances of the patented solar equipment were simulated using the RETScreen software considering that the building has double utilization: two apartments are used for tourist accommodation (considered to be booked half a year), and two apartments serves as a church rectory (whole year utilization). Using the patented flat solar water collector, the annual energy requirement for hot water preparation decreased with 45%, from 2845 kWh to 1292 kWh, when analyzing the church rectory. Considering the same hot water consumption profile but using the vacuum solar collector, the total heat delivered increased to 1615 kWh, even if the total collector's area decreased from 2.02 m 2 to 1.80 m 2 . The same vacuum system provided a 69% solar fraction (energy reduction from 1392 kWh/year to 960 kWh/year) for the accommodation apartments. The air heaters were mounded as windows shutters and have different areas for each orientation, thus different thermal energy production. Consequently, they were analyzed separately, and the heat delivered ranged from 646 kWh/year (East orientation) to 3479 kWh/year (South orientation). The total thermal energy provided by the solar air shutters was 5567 kWh/year, meaning approximatively 47% of the total energy required to maintain the interior temperature at 21 °C. Highlights: We present two new and high efficient solar thermal equipment (Volet'air ® -air heater and H2OSS ® -water heater). The patented renewable energy based equipment was used to refurbish a residential building, situated in Corsica, France. The overall performances of these systems were simulated using the RETScreen analysis tool. The simulations shown the overall energy reduction provided for the analyzed building.